Characterization and PCR Application of Family B DNA Polymerases from Thermococcus stetteri - Aleksandra A. Kuznetsova; Marina A. Soloveva; Elena S. Mikushina; Anastasia A. Gavrilova; Artemiy S. Bakman; Nikita A. Kuznetsov (Life)
DNA polymerases from the hyperthermophilic Archaea have attracted considerable attention as PCR enzymes due to their high thermal stability and proofreading 3′ → 5′ exonuclease activity. This study is the first to report data concerning the purification and biochemical characteristics of the Tst DNA polymerase from Thermococcus stetteri. Both the wild type Tst(wt) DNA polymerase and its chimeric form containing the P36H substitution—which reduces the enzyme’s affinity for the U-containing template and dUTP—and the DNA-binding domain Sso7d from S. solfataricus were obtained and analyzed. It was shown that Tst(wt) could effectively amplify up to 6-kb DNA fragments, whereas TstP36H–Sso7d could amplify DNA fragments up to 15 kb. It was found that TstP36H–Sso7d has superior PCR efficiency compared to the commonly used DNA polymerase PfuV93Q–Sso7d. For the amplification of a 2-kb DNA fragment, TstP36H–Sso7d required less than 10 s of extension time, whereas for PfuV93Q–Sso7d, the extension time was no less than 30 s. Steady-state kinetic assays revealed that the dNTP-binding affinity KdNTPm was the same for TstP36H–Sso7d and PfuV93Q–Sso7d, whereas the maximum rate of dNTP incorporation, kcat, was two orders of magnitude higher for TstP36H–Sso7d. Moreover, the incorporation of incorrect dNTP was not observed for TstP36H–Sso7d up to 56 °C, whereas for PfuV93Q–Sso7d, the extension of primer with incorrect dNTP was observed at 37 °C, supporting higher fidelity of TstP36H–Sso7d. The obtained data suggest that TstP36H–Sso7d may be a good candidate for high-fidelity DNA amplification.